Demographic factors and customers' bank choice criteria - Katarzyna Schmidt-Jessa (Central European Economic Journal (CEEJ), 2023)
The main objective of the presented research is to verify the influence of demographic factors on retail customers' bank selection criteria in Poland. We compiled descriptive and inferential statistics and did factor analysis using Principal Component Analysis. Our dataset is based on a sample of 515 questionnaires that were gathered in the first quarter of 2022. The results proved that there are significant differences among various groups of respondents and their bank selection criteria. The highest number of differences appear in the case of demographic factors of age, and then income and gender. In general, the most important factors are the cost of service and mobile and online banking. The study has direct implications for all types of banks that operate in developing markets, especially in East-Central Europe, as having this knowledge can help to appropriately target customers using bank selection criteria that are valued by different groups of customers.
Keywords: G21; J10; D90; 330; banks; selection criteria; customer behaviour; factor analysis; Poland